2017
DOI: 10.1371/journal.pone.0174978
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant radiotherapy after radical cystectomy for muscle-invasive bladder cancer: A retrospective multicenter study

Abstract: ObjectivesRadical cystectomy (RC) and pelvic lymph-node dissection (LND) is standard treatment for non-metastatic muscle-invasive urothelial bladder cancer (MIBC). However, loco-regional recurrence (LRR) is a common early event associated with poor prognosis. We evaluate 3-year LRR-free (LRRFS), metastasis-free (MFS) and overall survivals (OS) after adjuvant radiotherapy (RT) for pathological high-risk MIBC.Material and methodsWe retrospectively reviewed data from patients in 3 institutions. Inclusion criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Characteristics of 167 patients undergoing RC are depicted in Table S2. During follow up, 55 (33%) of 167 patients experienced recurrence with a median time from RC to diagnosis of 7 months (IQR, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Positive RM were found in 20 patients (12%) consisting of five cases of pT3 disease and 15 pT4.…”
Section: Positive Surgical Margins Are Associated With Local Recurrmentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristics of 167 patients undergoing RC are depicted in Table S2. During follow up, 55 (33%) of 167 patients experienced recurrence with a median time from RC to diagnosis of 7 months (IQR, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Positive RM were found in 20 patients (12%) consisting of five cases of pT3 disease and 15 pT4.…”
Section: Positive Surgical Margins Are Associated With Local Recurrmentioning
confidence: 99%
“…Local recurrence after RC has lethal potential and causes various symptoms including pain and hemorrhage. Many attempts have been made for the management of LR, including the development of risk stratification models, NAC, and adjuvant radiotherapy . Based on recent evidence that the addition of ICI to standard chemotherapy can result in significantly improved outcomes in treatment‐naive metastatic non‐small cell lung cancer, some phase II trials are ongoing to investigate the potential clinical benefits of GC chemotherapy combined with ICI for MIBC, such as NCT03294304 (nivolumab) and NCT02989584 (atezolizumab).…”
Section: Introductionmentioning
confidence: 99%
“…The results from a French multicenter study reported 5.2% and 9% of Grade ≥3 acute and late GI toxicity, respectively. 23 Another study by Zaghloul, et al 24 also reported 7% of late Gr 3 GI toxicities.…”
Section: Discussionmentioning
confidence: 96%
“…A recently published consensus contouring atlas for adjuvant bladder RT may help with standardization of target delineation for management of future patients and may lead to further improvements in patients treated with adjuvant RT [ 26 ]. A multi-institutional study from France has demonstrated good local control for patients with bladder cancer treated with adjuvant RT [ 27 ]. The authors reported using the Radiation Therapy Oncology Group (RTOG) atlas as a guide to define the Clinical Target Volume, suggesting that using published guidelines for target delineation can result in good clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%